L-theanine protects against D-galactose-induced aging in L6 skeletal muscle cells - Min Long; Qinyu Zhou; Xi Xiang; Kehong Liu; Wenjun Xiao (Journal of Functional Foods, 2024)
L-theanine (LTA) is a key component in tea plants and is commonly used as a functional ingredient and dietary supplement. In a recent study, we investigated the potential antiaging properties of LTA using a D-galactose-induced L6 skeletal muscle aging cell model. The results showed that LTA treatment improved cell viability and antioxidant enzyme activities while reducing levels of proinflammatory factors and advanced glycation end products. Additionally, LTA demonstrated the ability to decrease senescence-associated beta-galactosidase-positive cells, lower reactive oxygen species and MDA levels, preserve mitochondrial function, inhibit apoptosis, and alleviate cell cycle arrest in the G2/M phase. These protective effects may be attributed to the activation of the p53/p21/CDK4 pathway, regulation of cell cycle-related protein expression, promotion of cell proliferation, and regulation of apoptosis-related protein expression through the p53/Bax/Bcl-2 pathway.